Relationship Knowledge and Attitude of Nurses with Pain Management Practices in Neonates - Zubaidah Zubaidah; Elsa Naviati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
Pain is a subjective feeling and an unpleasant experience. In neonates, pain that is not handled properly can cause short-term and long-term effects. Repeated pain can affect the development of the baby later on. The purpose of this study was to identify the relationship between knowledge, attitudes of nurses and the practice of pain management in neonates. Method: The design of this study was descriptive associative with a cross sectional approach. The sample in this study involved 119 nurses who work in the Neonatal Intensive Care Unit (NICU). Data analysis using the Pearson correlation statistic test by identifying the relationship between respondent characteristics, knowledge, nurse attitudes and the practice of pain management in neonates. Results: Knowledge of nurses about pain management in neonates in the adequate category was 37%, nurses had negative attitudes towards pain management as much as 52.1%, and nurses who performed pain management well as much as 51.3%. There is a significant relationship between knowledge, attitudes of nurses and the practice of pain management in neonates (r = 0.715; p value = 0,000) and (r = 0.659; p value = 0,000). There is a need for a neonatal pain management training for nurses worked in high-risk neonatal ward to improve nurses' knowledge and attitudes.